(untitled) (Journal of Pedagogical Inventions and Practices, 2024)
In the context of the transition to a multi-level education system, the issues of environmental education of students are currently relevant. Therefore, special attention is paid to the issue of modeling environmental education of students. In this case, it was analyzed that environmental education in students of higher educational institutions will be very effective if various models are used in the formation of education